Application of CFD Numerical Simulations and Shape Optimization to Modify the Flow Characteristics of Throttle Valves - Alicja Dykas; Urszula Warzyńska (Energy Engineering and Control Systems, 2025)
The aim of the study was to perform a numerical analysis using the CFD method of oil flow through a hydraulic valve gap and to perform an optimisation of the gap shape with a view to linearising the valve characteristics. As part of the work, a flow analysis of the valve was carried out using numerical simulations. This made it possible to develop the characteristics of the studied valve. The optimisation process started with a shape sensitivity analysis to determine the effect of geometry on key flow parameters such as pressure drop. One of the resulting solutions selected on the basis of its functionality and technological manufacturing possibility was further analysed. The flow characteristics determined for the optimised design were compared with those of the original valve using statistical tools. It was shown that optimised geometry achieved a more linear characteristic, which will enable more precise throttle control using this valve.